Nondescent vaginal hysterectomy, a changing practice in Indian scenario for scar less surgery - 1Dr Sangam KumariSangam; Mitra, Nishi; Shrivastava, Sashibala (International Journal of Medical Research and Review, 2016)
Introduction: Hysterectomy is the most common operation performed next only to caesarean operation by gynaecologist. This decade has seen resurgence of hysterectomy by vaginal route for indication other than prolapse, may be due to better compliance by the patients. Aims and objective: This prospective observational study was conducted to assess safety, morbidity, and feasibility of nondescent vaginal hysterectomy. Method: All patients who fulfilled the criteria for the study were included in the study. NDVH was performed in the cases with adequate vaginal access, good uterine mobility and uterine size not exceeding 18 weeks. Different morcellation techniques were employed for bigger size uterus. Result: Total 50 patients underwent nondescent vaginal hysterectomy. 28 out of 50 patients were in 40 -49 years of age group. 98% of them were multiparous. Dysfunctional uterine bleeding (44%) was the most common indication followed by Pelvic inflammatory disease (26%). Morcellation techniques were employed in 33 cases (66%). Mean operating time was 79.6 minutes with average blood loss 110 ml and average duration of pain disappearance was on 4th day and hospital stay 6 days. Complications were minimal. Conclusion: Vaginal hysterectomy in non descended uterus is feasible, safe, associated with less morbidity and better compliance by patients.